Fetal pulmonary injury following single high-dose intra-amniotic betamethasone treatment in preterm goat kids - Antalyalı, Meltem (AVES, 2012)
OBJECTIVE: Fetal lung maturation is an extremely important process that is necessary for the survival of the neonates. Conventionally, corticosteroids are administered maternally for inducing fetal lung maturation in preterm fetuses. Alternatively, single-dose intra-amniotic (IA) treatment might be speculated to improve lung maturity. In the goat model, we recently showed that high-dose IA betamethasone (BM) was associated with an increased number of stillbirths and emphysematous changes. The aim of the present study is to expand our previous findings and evaluate the histopathological effects of IA injection of a single high-dose of BM 48 h before induced preterm delivery, using our previously collected specimens. MATERIAL AND METHODS: Five hair goat fetal lungs that had received 8 mg/kg IA BM at gestational day 118 (term, 150 days) and scheduled for preterm delivery by cesarean section at day 120 of gestation were examined pathologically. Specimens were stained with hematoxylin and eosin (HE) and were interpreted by light microscopy. RESULTS: The histopathological examination of the fetal lungs revealed edema, hemorrhage, slight inflammatory reaction, marked emphysema, and desquamation of the pneumocytes and bronchiolar or bronchial epithelial cells. CONCLUSION: High-dose IA BM administrations to induce lung maturation can paradoxically cause severe pathological lesions in the fetal lungs. These might explain the toxic effects we encountered with this mode of treatment.